On the phase behavior of sorbitol/water/H2/CO2 mixtures at high pressures and temperatures by in situ infrared spectroscopy - Bonnin, Isaline; Mereau, Raphaël; De Oliveira Vigier, Karine; Tassaing, Thierry (Comptes Rendus. Chimie)
The thermodynamic behavior of multi-component system, which includes sorbitol dissolved in water under CO2 and H2 pressure, is investigated by in situ infrared spectroscopy. Our study focuses on the gas phase of binary, ternary, and quaternary systems at temperatures ranging from 40 °C to 220 °C and at CO2 pressures between 30 and 120 bar, while maintaining a constant pressure of H2 at 30 or 60 bar. The influence of addition of sorbitol in the liquid aqueous phase and of H2 in the CO2-rich gas phase on the mutual solubility of CO2 and water is evaluated. In our experimental conditions (T< 220 °C and P< 120 bar), it is found that in such multi-component system, a water-rich liquid phase always coexists with a CO2-rich gas phase. Presence of sorbitol in the water-rich phase and H2 in the CO2-rich phase has a limited impact on the mutual solubility of water and CO2. Furthermore, sorbitol is not soluble in the CO2-rich phase and instead remains in the water-rich liquid phase over the thermodynamic range investigated.